COMPARISON OF BONDS PERFORMANCE WITH SYARIAH BONDS (SUKUK) - Sari, Kharisma Novita (Cattleya Darmaya Fortuna, 2024)
The purpose of this study is to determine the comparison of bond performance with sharia bonds (sukuk) in 2010-2023. This study uses quantitative calculations with a comparative type of research. The data used are sourced from secondary data from OJK. This study uses a population, namely the capitalization of sharia bond performance data (sukuk) compared to the capitalization of bond performance data, using the Sharpe, Jensen method for the 2010-2022 period (monthly data) in the Indonesian Capital Market. Data analysis was carried out using the Sharpe and Jensen methods and using the MANOVA test with the help of the SPSS statistical application program. The results of this study indicate that the performance of sukuk with bonds using the Sharpe and Jensen methods is not significantly different. This shows that the sukuk return and the bonds based on the Sharpe and Jensen methods that will be received will be relatively the same.